2018
DOI: 10.1097/md.0000000000010633
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of chronic kidney disease-associated pruritus among adult dialysis patients

Abstract: Chronic kidney disease (CKD)-associated pruritus is a common adverse symptom in patients with end-stage renal disease treated by dialysis. Herein, a systematic review and meta-analysis of the prevalence of CKD-associated pruritus among adult dialysis patients was conducted.An electronic search of PubMed, Web of Science, Elsevier, Wanfang, and Chinese National Knowledge Infrastructure databases was conducted from inception to November 23, 2016, and all cross-sectional studies that reported the prevalence of CKD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 57 publications
4
61
0
1
Order By: Relevance
“…In our study, a longer duration of CKD and hemodialysis had a very negligible effect on pruritus, which differs from another study in which a duration of hemodialysis of more than 2 years resulted in higher rates of pruritus (75% vs 25%) compared to those doing hemodialysis for less than 2 years [38]. The variation in pruritus prevalence reported in different studies may be due differences in study designs, selection of participants (e.g., study populations, races, and sample sizes), and the definition of CKD-aP [39]. In our study it was also revealed that hemodialysis machines were limited, and pressure from too many patients was a contributing factor to inadequate hemodialysis.…”
Section: Discussionmentioning
confidence: 88%
“…In our study, a longer duration of CKD and hemodialysis had a very negligible effect on pruritus, which differs from another study in which a duration of hemodialysis of more than 2 years resulted in higher rates of pruritus (75% vs 25%) compared to those doing hemodialysis for less than 2 years [38]. The variation in pruritus prevalence reported in different studies may be due differences in study designs, selection of participants (e.g., study populations, races, and sample sizes), and the definition of CKD-aP [39]. In our study it was also revealed that hemodialysis machines were limited, and pressure from too many patients was a contributing factor to inadequate hemodialysis.…”
Section: Discussionmentioning
confidence: 88%
“… 26 In a study of 223 patients on PD and 425 HD patients from Korea, the prevalence of at least mild pruritus was 62.5% in HD patients and 48.3% in patients on PD. 24 A meta-analysis of 6 cross-sectional prevalence studies (2 PD-only and 4 mixed HD and PD) showed a prevalence of CKD-aP of 56% (95% CI, 44%–68%) 28 ; however, the severity of this pruritus was not reported.…”
Section: Diagnosismentioning
confidence: 99%
“…Uremic pruritus is a common complication in patients with end-stage kidney disease. 1 The discomfort caused by pruritus can cause sleep disturbance, 2,3 depression, 3,4 and lack of concentration. 2 In hemodialysis patients, moderate and severe uremic pruritus is associated with higher mortality risk.…”
Section: Introductionmentioning
confidence: 99%